The Use of Continuous Audit to Improve the Effectiveness and Efficiency of Internal Audit Activities: A Practical Study of Distribution Sharia Company in Indonesia - Alwi, Mochamad (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
The implementation of technology has encouraged internal auditors to develop continuous audits as a practical method for obtaining useful information from a set of company electronic data related to internal audit activities at all stages. Continuous audit methods allow internal auditors to process the entire population of transaction data to identify risk and internal control weaknesses that are more likely to be the subject of an audit finding. XYZ is a distribution company that continues to expand its business with more than 200 branches in Indonesia especially in sharia business. However, a large number of branches and transactions face limited internal auditors, high audit costs, low levels of audit coverage, and potential human error, which are an obstacle. This research is a design science that proposes the use of DMADV six sigma methodology as a problem-solving method to enhance the effectiveness and efficiency of internal audit activity by applying technology and audit concept in the continuous audit system. This research revealed that the internal audit cost can decrease by 45,5% to IDR 528.000.000 and audit coverage can increase by almost double to 86,3% in a year.